INTERNALISASI NILAI SOPAN SANTUN DALAM KURIKULUM NASIONAL: ANALISIS DESKRIPTIF BUKU TEKS PPKN SEBAGAI INSTRUMEN MITIGASI KRISIS AKHLAK ANAK SD - Ade Supandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The issue of moral decline or the "moral crisis" among elementary school students, particularly regarding the diminishing values of politeness, presents a serious challenge to education in the digital era. The "Kurikulum Merdeka" (Independent Curriculum) was introduced with the vision of the "Pancasila Student Profile" to address these concerns. This study aims to analyze the internalization of politeness values in the Pancasila Education (PPKn) textbooks of the Independent Curriculum as a tool for addressing the moral crisis. This research employs a qualitative descriptive approach with a content analysis method. The research objects are the Primary Textbooks of Pancasila Education for Grades I and IV published by the Ministry of Education and Culture. Data were analyzed using the Miles and Huberman model, which includes condensation, data display, and conclusion drawing. The findings indicate that the textbooks systematically integrate politeness values through verbal, gestural, and social typologies. However, the existing narratives primarily focus on face-to-face interactions and have not addressed digital etiquette. The Independent Curriculum PPKn textbooks are adequate as cognitive tools for introducing politeness values, but their effectiveness in addressing the moral crisis requires reinforcement through teacher role-modeling and adaptation to communication ethics in cyberspace.